Electrocardiogram of Clinically Healthy Mithun (Bos frontalis): Variation among Strains - Sagar Sanyal; Pradip Kumar Das; Probal Ranjan Ghosh; Kinsuk Das; Kezha V. Vupru; Chandan Rajkhowa; Mohan Mondal (Veterinary Medicine International)
A study was conducted to establish the normal electrocardiogram in four different genetic strains of mithun (Bos frontalis). Electrocardiography, cardiac electrical axis, heart rate, rectal temperature and respiration rate were recorded in a total of 32 adult male mithun of four strains (𝑛=8 each). It was found that the respiration and heart rates were higher (𝑃<.05) in Manipur than other three strains. Amplitude (𝑃<.05) and duration of P wave and QRS complex differed (𝑃<.01) among the strains. Mizoram strain had the highest amplitude and duration of P wave and QRS complex. On the other hand, higher (𝑃<.05) amplitude and duration of T wave were recorded in Arunachalee and Mizoram strains. The mean electrical axis of QRS complex that were recorded for Arunachalee and Manipur strains were similar to that reported for other bovine species; whereas the electrical axis of QRS for Nagamese and Mizoram strains were more close to feline and caprine species, respectively. In conclusion, electrocardiogram of mithun revealed that the amplitude and duration of P wave, QRS complex and T wave were different among four different genetic strains of mithun and the electrical axis of QRS complex for Nagamese and Mizoram mithuns are dissimilar to bovine species.